TAFSIR OF EDUCATION IN THE THOUGHT OF MUHAMMAD ABDUH - Mujrimin, Bayu (Mandeh : Jurnal Pendidikan Islam, 2024)
This study aims to examine the interpretation of educational verses in the thought of Muhammad Abduh and its relevance to the development of contemporary Islamic curriculum. Using a qualitative approach and library research method, the study analyzes Abduh’s interpretation of several key educational verses such as Surah Al-‘Alaq: 1–5 and At-Tawbah: 122. The findings indicate that Abduh emphasized the importance of reason, intellectual freedom, and the reform of Islamic education based on rationality and morality. His exegesis is not merely textual but also contextual, responding to the challenges of his time. The relevance of Abduh’s ideas is evident in the conception of an integrative curriculum that harmonizes religious and modern sciences, aiming to produce rational, responsible, and productive individuals. This research recommends the integration of reformist tarbawi values into the design of Islamic curriculum to ensure greater adaptability in the face of global developments.